The Procyclicality of Political Trust in Spain - Caballero, Gonzalo; Álvarez-Díaz, Marcos (Panoeconomicus, 2018)
Political trust has been considered a necessary condition for good democratic and economic performance over time. The grave economic crisis that started in 2008, which is known as the Great Recession, has deteriorated the level of political trust in several countries. Some authors have shown that those countries with an increasing level of unemployment experienced a sharp decline in political trust. In particular, the political distrust in Spain has suffered a high increase since the Great Recession. This paper tests the procyclicality of political trust in Spain through the analysis and modeling of the relationship between political trust and business cycle in Spain over the period 1996-2015. The cross correlation analysis, the Granger causality test, and the autoregressive distributed lag (ARDL) bounds testing approach coherently conclude the procyclicality of political trust in Spain. The unemployment rate shows a negative and statistically significant influence on political trust four quarters later. Key words: Political trust, Procyclicality, Economic crisis, Statistical analysis, Spain. JEL: C22, C51, E32, P16. Političko poverenje se smatra potrebnim uslovom za dobre demokratske i ekonomske performanse tokom vremena. Teška ekonomska kriza koja je započela 2008. godine, poznata kao Velika Recesija, pogoršala je nivo političkog poverenja u nekoliko zemalja. Neki autori su pokazali da su zemlje sa rastućim stepenom nezaposlenosti doživele oštar pad političkog poverenja. Konkretno, političko nepoverenje u Španiji pretrpelo je veliki porast od Velike Recesije. U radu se testira procikličnost političkog poverenja u Španiji kroz analizu i modeliranje odnosa između političkog poverenja i poslovnog ciklusa u Španiji tokom perioda 1996-2015. Analiza unakrsne korelacije, Grendžerov test uzročnosti i ARDL metoda zasnovanog na graničnim kritičnim vrednostima, koherentno zaključuju procikličnost političkog poverenja u Španiji. Stopa nezaposlenosti pokazuje negativan i statistički značajan uticaj na političko poverenje četiri tromesečja kasnije. Ključne reči: političko poverenje, procikličnost, ekonomska kriza, statistička analiza, Španija.